The Quality of Your Network Matters: Professional Connections and Mutual Fund Performance - Chien, Jimmy; Duanmu, Jun; McCumber, William R. (Journal of Applied Business and Economics, 2023)
We examine whether the professional networks of mutual fund managers serve as a conduit of information that benefits fund investors. We find investors enjoy higher returns when their funds are led by well-connected managers. A long-short portfolio strategy of funds ranked upon the quality of fund managers’ networks yields positive and statistically significant mean and risk-adjusted returns to investors for both in-sample and out-of sample testing. The results suggest that manager networks enable information flows that benefit fund investors. Additionally, we present evidence that fund managers do not act on material non-public information gathered from contemporaneous board appointments.